2013
DOI: 10.2217/imt.12.139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immune Modulation Therapy on Cardiac Function and T-bet / GATA-3 Gene Expression in Aging Male Patients with Chronic Cardiac Insufficiency

Abstract: Immune modulation improved cardiac function of CCI patients and was associated with amelioration of T-helper superficial transcription factor polarization and its related cytokine imbalance. Immune modulation might be a new treatment strategy for aging CCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…CRP levels are elevated in CHF and increasing levels are associated with increasing morbidity and mortality in ischemic and non-ischemic etiologies (Nakagomi et al, 2010). In this study, we found higher levels of NT-proBNP and CRP in the two DCM groups than in the normal control group, and in our previous study, NT-proBNP and CRP levels were negatively correlated with LVEF (Han et al, 2013). The DCM heart presumably undergoes a complex series of changes in neurohumoral mechanisms such as the sympathetic nervous and renin-angiotensin-aldosterone systems to compensate for the reduction in cardiac contractility, which are likely to affect cardiac gene expression resulting in electrical remodeling, ultimately evolving to cardiac arrhythmia, pump failure, and sudden death (Tsutamoto et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…CRP levels are elevated in CHF and increasing levels are associated with increasing morbidity and mortality in ischemic and non-ischemic etiologies (Nakagomi et al, 2010). In this study, we found higher levels of NT-proBNP and CRP in the two DCM groups than in the normal control group, and in our previous study, NT-proBNP and CRP levels were negatively correlated with LVEF (Han et al, 2013). The DCM heart presumably undergoes a complex series of changes in neurohumoral mechanisms such as the sympathetic nervous and renin-angiotensin-aldosterone systems to compensate for the reduction in cardiac contractility, which are likely to affect cardiac gene expression resulting in electrical remodeling, ultimately evolving to cardiac arrhythmia, pump failure, and sudden death (Tsutamoto et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…Interferon-γ (IFN-γ) is the signature cytokine of Th1 cells and interleukin-4 (IL-4) is the corresponding signature cytokine of Th2 cells. GATA-binding protein 3 (GATA-3) is a Th2-specific transcription factor, which is upregulated during Th2 differentiation (9,10). The transcription factor T-box expressed in T cells (T-bet) controls the expression of the hallmark Th1 cytokine IFN-γ (11).…”
Section: Cd4mentioning
confidence: 99%
“…GATA-3 is a transcription factor revealed to be specifically expressed in Th2 cells, whereas T-box protein expressed in T cells (T-bet) is a transcription factor specifically expressed in Th1 cells. GATA-3 and T-bet have been reported to modulate gene expression during T cell differentiation, thus serving a critical role in the development of Th1 and Th2 lineages ( 4 , 5 ). However, the molecular mechanisms underlying allergic rhinitis are complex and involve other pathways apart from an aberrant Th2 response.…”
Section: Introductionmentioning
confidence: 99%